Results of a pilot study of endoscopic screening of first degree relatives of colorectal cancer patients in Italy. Issue 4 (August 1997) - Colombo, L; Corti, G; Magrì, F; Marocchi, A; Brambilla, P; Crespi, C; Manieri, L; Ghezzi, S; Giannone, D; Merlino, L; Mocarelli, P
Abstract : STUDY OBJECTIVE: Screening recommendations for colorectal cancer include sigmoidoscopy in asymptomatic, average risk persons aged 50 and over and colonoscopy every three to five years in high risk groups. Little is known about the eligible population's compliance with endoscopic screening. This is the first Italian report of an endoscopic screening programme for colorectal cancer patients' relatives. DESIGN: In 1986, a pilot project for colorectal cancer screening by endoscopy in high risk subjects was started in the Desio (Milan, Italy) public health service region. The results obtained after seven years are described. SETTING: The names of 536 inhabitants with colorectal cancer diagnosed between January 1975 and December 1984 and their relatives' addresses were obtained from the Regione Lombardia Health System records and from the municipal registry offices respectively. PARTICIPANTS: From October 1986 to October 1993, 778 first degree relatives aged 20-75 were offered colonoscopy. MAIN RESULTS: After seven years, 233 (29.9%) had undergone endoscopic examination, mostly up to the splenic flexure. Being > 60 in age at the start of the programme negatively affected the participation (p < 0.05). Two cancers were detected and adenomatous polyps were found in another 24 of those screened (frequencies 0.9% and 10.3% respectively). Male gender (p < 0.05), increasing age in males (p < 0.01), and two or more affected relatives in females (p < 0.01) positively affected the frequency of polyps detection. CONCLUSION: These results suggest that about 30% of the eligible population would comply at least with sigmoidoscopic screening. The collaboration of family doctors and more widespread public information about the ability to cure colorectal cancer are necessary for better compliance.